A prospective randomized controlled trial for comparison of oral misoprostol with methyl ergometrine in the third stage of labour for prevention of post-partum haemorrhage - Gore, Sushma; Padmawar, Atul; Pathan, Sabir Khan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Near about 11% of women having live births have severe PPH (Globally 14 million women per year). About 3.9% of vaginal deliveries and 6.4% of cesarean section get PPH. Near about 1.4 million women die of PPH every year. Frequency of PPH is related to management of third stage of labour. Objective of the study was to compare the efficacy of misoprostol with conventional oxytocics for active management of third stage of labour. Methods: The present study was carried out in tertiary care teaching hospital for a period of three years from June 2007-May 2010. A total of 364 study participants who reported to labour ward with labour pains in latent phase and subsequently went in spontaneous labour were enrolled and randomly distributed to two groups and given oral misoprostol and i.v. ergometrine. Results: The mean age in Group A was 23.17±2.55 and 24.31±3.28 respectively. It was observed that most the study participants in both the groups had the duration of third stage of labour in between 10-14 minutes i.e. 29% in Group A and 36.3% in Group B respectively. The duration of third stage of labour was significantly more in Group B compared to Group A. Conclusions: Misoprostol is a promising drug in the management of third stage of labour for the prevention of post- partum haemorrhage.